2022
DOI: 10.3390/genes13040603
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Detection of Copy Number Variants in Chinese Indigenous Horse Breeds and Verification of CNV-Overlapped Genes Related to Heat Adaptation of the Jinjiang Horse

Abstract: In the present study, genome-wide CNVs were detected in a total of 301 samples from 10 Chinese indigenous horse breeds using the Illumina Equine SNP70 Bead Array, and the candidate genes related to adaptability to high temperature and humidity in Jinjiang horses were identified and validated. We determined a total of 577 CNVs ranging in size from 1.06 Kb to 2023.07 Kb on the 31 pairs of autosomes. By aggregating the overlapping CNVs for each breed, a total of 495 CNVRs were detected in the 10 Chinese horse bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(24 citation statements)
references
References 52 publications
5
18
1
Order By: Relevance
“…In addition, although several CNVRs were observed in all the chromosomes ( Figure 2 ), the coverage of CNVRs in each chromosome varied from 1.9% in ECA14 and ECA16 to 19.2% in ECA12. These results in terms of variability agree with most of the previous studies carried out on horses [ 9 , 12 , 13 , 14 , 16 , 19 , 20 , 21 , 22 , 23 , 24 ]. However, several of them reported that ECA12 is particularly enriched in CNVRs, including a cluster of genes associated with the development of olfactory receptors (ORs) [ 13 , 18 , 19 ].…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…In addition, although several CNVRs were observed in all the chromosomes ( Figure 2 ), the coverage of CNVRs in each chromosome varied from 1.9% in ECA14 and ECA16 to 19.2% in ECA12. These results in terms of variability agree with most of the previous studies carried out on horses [ 9 , 12 , 13 , 14 , 16 , 19 , 20 , 21 , 22 , 23 , 24 ]. However, several of them reported that ECA12 is particularly enriched in CNVRs, including a cluster of genes associated with the development of olfactory receptors (ORs) [ 13 , 18 , 19 ].…”
Section: Resultssupporting
confidence: 92%
“…Although the number of deletions and duplications detected differed among chromosomes ( Table S1 ), an interesting finding was the fact that the number of duplications (12,987) exceeded the number of deletions (6915) in most of them, with the sole exception of ECA1, ECA4, and ECA29, in which the opposite pattern was observed. These results are similar to other studies [ 9 , 12 , 13 , 14 , 16 , 24 ], which reported more gains than losses in several horse populations. Although CNVs can be a source of wide variability at the same locus, duplications are more likely to occur in large CNVs than deletions, since they are more tolerated by the genome since no loss of genetic material occurs [ 40 , 41 ].…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations